2021
DOI: 10.3390/pharmaceutics13111953
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Injectable In Situ-Forming Hydrogels for Intratumoral Treatment

Abstract: Chemotherapy has been linked to a variety of severe side effects, and the bioavailability of current chemotherapeutic agents is generally low, which decreases their effectiveness. Therefore, there is an ongoing effort to develop drug delivery systems to increase the bioavailability of these agents and minimize their side effects. Among these, intratumoral injections using in situ-forming hydrogels can improve drugs’ bioavailability and minimize drugs’ accumulation in non-target organs or tissues. This review d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 100 publications
0
22
0
Order By: Relevance
“…Additionally, in situ forming hydrogels, existing in the liquid state at ambient temperature but experiencing a phase transition once injected into the body, can be combined with anti-cancer drugs or protein-based therapeutics, and are ideal candidates for various cancer therapies, since they provide multiple benefits such as having minimal invasiveness, prolonging the drug delivery, increasing the drugs' bioavailability, diminishing the side effects, and enhancing the patient compliance. Several obstacles of these systems, including immunogenicity, toxic cross-linking agents, and biodegradability under the tumor microenvironment conditions, should be taken into account in future evaluations to achieve optimized clinically applicable systems [267,268]. Specifically, in the case of protein-based in situ hydrogels, although they offer tissue-specific gelation and controlled release of their cargo, the rational design of them can be challenging, as the hydrogel's structure and characteristics are highly dependent upon the structure of their building blocks [269].…”
Section: Summary Challenges and Outlookmentioning
confidence: 99%
“…Additionally, in situ forming hydrogels, existing in the liquid state at ambient temperature but experiencing a phase transition once injected into the body, can be combined with anti-cancer drugs or protein-based therapeutics, and are ideal candidates for various cancer therapies, since they provide multiple benefits such as having minimal invasiveness, prolonging the drug delivery, increasing the drugs' bioavailability, diminishing the side effects, and enhancing the patient compliance. Several obstacles of these systems, including immunogenicity, toxic cross-linking agents, and biodegradability under the tumor microenvironment conditions, should be taken into account in future evaluations to achieve optimized clinically applicable systems [267,268]. Specifically, in the case of protein-based in situ hydrogels, although they offer tissue-specific gelation and controlled release of their cargo, the rational design of them can be challenging, as the hydrogel's structure and characteristics are highly dependent upon the structure of their building blocks [269].…”
Section: Summary Challenges and Outlookmentioning
confidence: 99%
“…Secondly, there are several challenges derived from the use of hydrogels for intra-tumoral injection. It has been reported that a majority of injected depots might cause serious inflammation at the site of injection; therefore, the immunogenicity of in situ-forming hydrogels to healthy tissues adjacent to the injected site must be studied carefully [ 236 ]. In addition to this, selecting a suitable polymer with high biocompatibility, biodegradability, and safety profile is very challenging, yet it is extremely essential.…”
Section: Authors’ Opinion On the Future Perspectives Of Locoregional ...mentioning
confidence: 99%
“…In addition to this, selecting a suitable polymer with high biocompatibility, biodegradability, and safety profile is very challenging, yet it is extremely essential. Hydrogel materials must be biodegradable in tumour microenvironment and not just in hypothetical conditions, degrading at a similar rate to the tumour’s size reduction [ 236 ]. However, in the systems where inorganic materials were introduced for the theragnostic purpose, despite the overall reduction in biodegradability of the systems, their long-term stability is greatly enhanced.…”
Section: Authors’ Opinion On the Future Perspectives Of Locoregional ...mentioning
confidence: 99%
“…There are several reports using natural materials such as biocompatible hyaluronic acid (HA), cellulose, silk, and collagen as injectable in situ -forming hydrogel drug carriers [ [25] , [26] , [27] , [28] , [29] , [30] ]. Among them, an injectable HA hydrogel was reported to temporarily maintain its elastic and viscose integrity as a depot under physiological conditions [ 31 ].…”
Section: Introductionmentioning
confidence: 99%